2006
DOI: 10.4103/0378-6323.25636
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations in patients with chronic renal failure on hemodialysis

Abstract: CRF is associated with a complex array of cutaneous manifestations caused either by the disease or by treatment. The commonest are xerosis and pruritus and the early recognition of cutaneous signs can relieve suffering and decrease morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
60
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 11 publications
11
60
4
1
Order By: Relevance
“…It was seen in study done by Udaykumar et al 11 Cancerous and precancerous lesions were not seen in this study. It was seen in few patients in other studies.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…It was seen in study done by Udaykumar et al 11 Cancerous and precancerous lesions were not seen in this study. It was seen in few patients in other studies.…”
mentioning
confidence: 49%
“…The survival of red blood cells is reduced by approximately one-third in HD patients. 11 Common nail changes seen in this study was leukonychia in 11 patients followed by Lindsay's nail in 6 patients, onycholysis in 4 patients and subungual hyperkeratosis in 3 patients. In other studies nail changes observed were leukonychia, koilonychia, subungual hyperkeratosis, onycholysis, Mees' lines, Muehrcke's lines, Beau's lines and splinter hemorrhage.…”
Section: -4mentioning
confidence: 99%
See 2 more Smart Citations
“…Yellowing of the skin may be seen due to the deposition of carotenoids and urochromes within the skin and subcutaneous tissue. Hyperpigmentation is most prominent in sun-exposed areas and is attributed to increase in skin melanin due to excessive beta-melanocyte stimulating hormone [4]. …”
Section: Nonspecific Skin Changesmentioning
confidence: 99%